Informatics in Control, Automation and Robotics Volume 1 - Tan, Honghua (Springer eBooks., 2011)
Session 1 includes 109 papers selected from 2011 3rd International Asia Conference on Informatics in Control, Automation and Robotics (CAR 2011), held on December 24-25, 2011, Shenzhen, China. This session will act as an international forum for researchers and practitioners interested in the advances in and applications of Intelligent Control Systems. It is an opportunity to present and observe the latest research, results, and ideas in these areas. Intelligent control is a rapidly developing, complex, and challenging field of increasing practical importance and still greater potential. Its applications have a solid core in robotics and mechatronics but branch out into areas as diverse as process control, automotive industry, medical equipment, renewable energy and air conditioning. So, this session will aim to strengthen relationships between industry, research laboratories and universities. All papers published in session 1 will be peer evaluated by at least two conference reviewers. Acceptance will be based primarily on originality and contribution.